Predicting incident radiographic knee osteoarthritis through quantitative meniscal lesion parameters: data from the osteoarthritis initiative - Kaida Bo; Xiangpeng Xie; Xin Liu; Jianliang Ou; Yuanyi Zhang; Xu Wang; Shuo Yang; Wei Zhang; Lelei Zhang; Jun Chang (BMC Musculoskeletal Disorders, 2024)
Abstract Background This study investigates the potential of novel meniscal parameters as predictive factors for incident radiographic knee osteoarthritis (ROA) over a span of four years, as part of the Osteoarthritis Initiative (OAI) study. Objectives Quantitative measurements of meniscal parameters alteration could serve as predictors of OA’s occurrence and progression. Methods and materials A nested matched case-control study design was used to select participants from OAI study. Case knees (n = 178) were defined as those with incident ROA (Kellgren Lawrence Grade (KLG) 0 or 1 at baseline (BL), evolving into KLG 2 or above by year 4). Control knees were matched one-to-one by sex, age and radiographic status with case knees. The mean distance from medial-to-lateral meniscal lesions [Mean(MLD)], mean value of tibial plateau width [Mean(TPW)] and the mean of the relative percentage of the medial-to-lateral meniscal lesions distance [Mean(RMLD)] were evaluated through coronal T2-weighted turbo spin echo (TSE) MRI at P-0 (visit when incident ROA was found on radiograph), P-1(one year prior to P-0) and baseline, respectively. Using the imaging data of one patient, the mechanism was investigated by finite element analysis. Results Participants were on average 60.22 years old, predominantly female (66.7%) and overweight (mean BMI: 28.15). Mean(MLD) and Mean(RMLD) were significantly greater for incident knees compared to no incident knees at baseline, P-1 and P-0. [Mean(MLD), Mean(RMLD); (42.56–49.73) mean ± (7.70–9.52) mm SD vs. (38.14–40.78) mean ± (5.51–7.05)mm SD; (58.61–68.95) mean ± (8.52–11.40) mm SD vs. (52.52–56.35) mean ± (6.53–7.85)mm SD, respectively]. Baseline Mean(MLD) and Mean(RMLD), [Adjusted OR, 95%CI: 1.11(1.07 to 1.16) and 1.13(1.09 to 1.17), respectively], were associated with incident ROA during 4 years, However, Mean(TPW) [Adjusted OR, 95%CI: 0.98(0.94 to 1.02)] was not associated with incident ROA during 4 years. While Mean(TPW) at P-1 and P-0 was not associated with the risk of incident ROA, Mean(MLD) and Mean(RMLD) at P-1 and P-0 were significantly positively associated with the risk of incident ROA. Conclusions The meniscal parameters alteration could be an important imaging biomarker to predict the occurrence of ROA.